From source-to-sink: The Late Permian SW Gondwana paleogeography and sedimentary dispersion unraveled by a multi-proxy analysis. (October 2016) - Alessandretti, Luciano; Machado, Rômulo; Warren, Lucas Veríssimo; Assine, Mario Luis; Lana, Cristiano
Abstract: The Late Permian sedimentary succession of the Paraná Basin, southern Brazil, provide a valuable source of information about sediment provenance, tectonic processes and, consequently, the paleogeography of the southwestern Gondwana supercontinent. In order to understand the patterns of sedimentary dispersal and reconstruct the Late Permian source-to-sink dynamic, we report a complete series of U-Pb ages and Hf isotopic compositions of detrital zircons from the Rio do Rasto Formation sandstones allied with detailed paleocurrent and sedimentologic data. Our integrated provenance study reveals a consistent sediment transport from the south to the north and northwest. According to the evaluation of zircon ages and Hf isotopes, it was possible to determine four distinct source areas: (i) a distant Late Paleozoic active magmatic arc located in the southwestern Gondwana margin (i.e. Gondwanides Orogen), corresponding to the North Patagonian Massif; (ii) recycling of orthoquartzites from the uplifted Paleozoic Ventania Fold Belt and immature sandstones from the Claromecó Foreland Basin in central-eastern Argentina and the Silurian-Devonian successions of the southern Paraná Basin (central-northern Uruguay) and North Patagonian Massif; (iii) exhumed areas of the Archean-Paleoproterozoic basement and Neoproterozoic to Early Paleozoic mobile belts of the Damara in southwestern Africa and Ribeira Fold Belt in Uruguay and southern Brazil; and (iv) southeastward provenance of Grenvillian (1.2–1.0 Ga) zircons coming from the mafic to intermediate Mesoproterozoic igneous units of the Namaqua-Natal Belt in South Africa and Namibia. These data allow us to argue that sediments deposited in the Paraná Basin during the Late Permian come from both short- and long-distance source areas. In this context, an important population of Permian detrital zircons comes from the Gondwanides Orogen in the south, probably carried by transcontinental alluvial systems. Close to the source area, antecedent river channels would have eroded older sedimentary rocks of the Ventania Fold Belt, Claromecó and Chaco-Paraná basins and North Patagonian Massif, crosscutting a peripheral bulge and flowing towards the alluvial plain of the intraplate setting to areas further north. Concomitantly, these sediments are reworked by strong winds that even helped carrying the grains to the Paraná Basin depositional site. Graphical abstract: Highlights: We report a complete series of U-Pb ages and Hf isotopic compositions of detrital zircons from the Rio do Rasto Formation. Paleocurrent data reveals a consistent sediment-routing system from the south to the north and northwest. Sediments deposited in the Paraná Basin during the Late Permian come from both short- and long-distance source areas.